Cover Picture: Charge‐Induced Unzipping of Isolated Proteins to a Defined Secondary Structure (Angew. Chem. Int. Ed. 10/2016). Issue 10 (4th February 2016) - González Flórez, Ana Isabel; Mucha, Eike; Ahn, Doo‐Sik; Gewinner, Sandy; Schöllkopf, Wieland; Pagel, Kevin; von Helden, Gert
Abstract : Charge‐induced unzipping of isolated proteins leads to a defined secondary structure characterized by intramolecular C5 hydrogen bonds. The cover picture shows how Coulomb repulsion can pull apart helical elements to form an extended linear conformation similar to a single‐strand β sheet. As G. von Helden and co‐workers report in their Communication onpage 3295 ff., this conformation is likely a universal form of secondary structure in highly charged protein ions.